Comparison of web applications development using Spring MVC and Vaadin - Tomczyk, Łukasz; Pańczyk, Beata (Journal of Computer Sciences Institute, 2018)
The article presents the results of web application development effectiveness on Java platform in 1.8 version using Spring MVC and Vaadin frameworks. The comparative analysis was conducted with test applications, implementing the same functionalities in both technologies.